2004
DOI: 10.1007/s10038-004-0172-1
|View full text |Cite
|
Sign up to set email alerts
|

An association analysis between ApoA1 polymorphisms and the high-density lipoprotein (HDL) cholesterol level and myocardial infarction (MI) in Japanese

Abstract: Association studies were performed to confirm the effect of polymorphisms in apolipoprotein A1 (ApoA1) on the high-density lipoprotein cholesterol (HDL-C) level and the incidence of myocardial infarction (MI). A sequence analysis identified nine polymorphisms in ApoA1. After considering linkage disequilibrium, four polymorphisms in ApoA1and four polymorphisms in the 5¢-flanking regions and 3¢-flanking regions from the JSNP database were determined in 1,880 subjects recruited from the Suita study, which represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
2
16
2
Order By: Relevance
“…In brief, the APOA1 (À75G > A) polymorphism has been found to be associated by some with elevated APOA1 and HDLcholesterol concentrations [39][40][41][42][43], suggesting a protective effect for the minor allele. However, these findings are far from being consistent and they appear to be significantly modified by environmental factors [44]. The variants À482C > T and À455T > C at the insulin response element in the promoter region of the APOC3 gene, which are in strong LD with the most studied variant APOC3-SstI (3238C > G) [23 ,45], primarily affect plasma triglyceride concentrations [46,47]; and carriers of the minor allele may have an increased risk of coronary artery disease (CAD) [46].…”
contrasting
confidence: 46%
“…In brief, the APOA1 (À75G > A) polymorphism has been found to be associated by some with elevated APOA1 and HDLcholesterol concentrations [39][40][41][42][43], suggesting a protective effect for the minor allele. However, these findings are far from being consistent and they appear to be significantly modified by environmental factors [44]. The variants À482C > T and À455T > C at the insulin response element in the promoter region of the APOC3 gene, which are in strong LD with the most studied variant APOC3-SstI (3238C > G) [23 ,45], primarily affect plasma triglyceride concentrations [46,47]; and carriers of the minor allele may have an increased risk of coronary artery disease (CAD) [46].…”
contrasting
confidence: 46%
“…Plasma HDL cholesterol and ApoA1 levels are associated with lower CVD risk, especially MI risk. 23,24 However, atherosclerosis-related oxidative stress and inflammation lead to oxidation and other modifications of mature ApoA1, a phenomenon that can switch atheroprorective properties of native apoA1 to proatherogenic properties of modified ApoA1. 25 ApoA1 modification could induce formation of ApoA1-specific IgG antibodies that exhibit pro-inflammatory properties.…”
Section: Atherosclerosis-associated Autoimmunitymentioning
confidence: 99%
“…[12][13][14] We excluded young subjects from the control group, because they might develop MI in their 50 s and 60 s. The MI group consisted of 379 randomly selected inpatients and outpatients with documented MI who were admitted to the Division of Cardiology at the National Cardiovascular Center between May 2001 and April 2003 (MI group). 15 The characteristics of the study population are shown in Table 1. All subjects gave written informed consent and the present study was approved by the Ethics Committee of the National Cardiovascular Center and by the Committee on Genetic Analysis and Gene Therapy of the National Cardiovascular Center.…”
Section: Study Populationmentioning
confidence: 99%